2022
DOI: 10.1093/ajhp/zxac102
|View full text |Cite
|
Sign up to set email alerts
|

National trends in prescription drug expenditures and projections for 2022

Abstract: Disclaimer In an effort to expedite the publication of articles, AJHP is posting manuscripts online as soon as possible after acceptance. Accepted manuscripts have been peer-reviewed and copyedited, but are posted online before technical formatting and author proofing. These manuscripts are not the final version of record and will be replaced with the final article (formatted per AJHP style and proofed by the authors) at a later time. Purpose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 12 publications
3
21
0
Order By: Relevance
“…The data of this study indicated that, the total number of prescriptions were much higher than previous local study conducted in 2009 [17] and finding of this study was comparable to the study conducted between years 1997-2002 by which referring to dramatic changes in prescribing medicines trend in the public sector noting that average number of drugs per prescription was less than the current work [13].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The data of this study indicated that, the total number of prescriptions were much higher than previous local study conducted in 2009 [17] and finding of this study was comparable to the study conducted between years 1997-2002 by which referring to dramatic changes in prescribing medicines trend in the public sector noting that average number of drugs per prescription was less than the current work [13].…”
Section: Discussionsupporting
confidence: 60%
“…In compared to previous local studies an average consultation time is as twice as before but it could be still too short to get patient history, to examine the patient, to decide about drugs needed to be written on the prescription or to give advice to the patient [17].…”
Section: Discussionmentioning
confidence: 93%
“…Biosimilars will enter the markets in the context of COVID-19 (Schulze et al 2022a , b ; Tichy et al 2022 ), it depends on a robust and scalable manufacturing with excellent productivity. PI is a key trend involving process strategies.…”
Section: Discussionmentioning
confidence: 99%
“…US medication pricing is complex and varies by care setting. Recent US and Canadian reports have shown increasing rates of prescription medication spending in both inpatient and outpatient settings (26)(27)(28). A US health insurance organization reported that for 10 specialty medications within the top 25 medications by 2019 Medicare Part B spending (9 intravenous immunotherapy agents, 1 intramuscular neuromuscular blocker), hospital and physician office charges were 108% and 22% higher, respectively, compared to specialty pharmacies (29).…”
Section: Limitationsmentioning
confidence: 99%